Intermittent Growth of a Newly-Born Volcanic Island and Its Feeding System Revealed by Geological and Geochemical Monitoring 2013–2020, Nishinoshima, Ogasawara, Japan - Maeno, Fukashi; Yasuda, Atsushi; Hokanishi, Natsumi; Kaneko, Takayuki; Tamura, Yoshihiko; Yoshimoto, Mitsuhiro; Nakano, Shun; Takagi, Akimichi; Takeo, Minoru; Nakada, Setsuya (Frontiers in Earth Science, 2021)
The island-forming Nishinoshima eruptions in the Ogasawara Islands, Japan, provide a rare opportunity to examine how the terrestrial part of the Earth surface increases via volcanism. Here, the sequence of the recent eruptive activity of Nishinoshima is described based on geological and geochemical monitoring and the formation process of the new volcanic island and the cause of the temporal changes in the magma chemistry are discussed. The growth of Nishinoshima was sustained by the effusion of low-viscosity andesite lava flows. The lava flows spread radially with numerous branches, resulting in compound lava flows. This process made the main contribution to the construction of the solid foundation of the island; however, pyroclastic eruptions further developed the subaerial volcanic edifice. The duration of the eruptive episodes was initially 2 years but gradually shortened to a week, with a decreasing eruptive volume and discharge rate with time. However, the latest episode was the most intense and largest, with a magma discharge rate on the order of 106 m3/day. The temporal change in the chemical composition of the magma indicates that more mafic magma was involved in the later episodes. The initial andesite magma with ~60 wt.% SiO2 changed to basaltic andesite magma with ~55 wt.% SiO2, including olivine phenocryst, during the last episode. The eruptive behavior and geochemical characteristics suggest that the recent Nishinoshima eruptions are fueled by magma resulting from the mixing of silicic and mafic components in a shallow reservoir and by magma episodically supplied from deeper reservoirs. The lava effusion and the occasional explosive eruptions, sustained by the discharge of magma caused by the interactions of these multiple magma reservoirs at different depths, contributed to the formation and growth of the new Nishinoshima volcanic island. Comparisons with several examples of island-forming eruptions in the shallow sea indicate that a long-lasting voluminous lava effusion with a discharge rate on the order of at least 104 m3/day (annual average) to 105 m3/day (monthly average) is required for the formation and growth of a new volcanic island that can survive sea-wave erosion for a long time.